The role of Big Data Analytics in Financial Decision-Making and Strategic Accounting - Thanasas, Georgios L.; Kampiotis, Georgios (Technium Business and Management, 2024)
This paper examines the transformative impact of big data analytics on the accounting profession, focusing on its application in financial forecasting, risk management, fraud detection, and strategic decision-making. By utilizing advanced tools such as Hadoop, Apache Spark, and machine learning algorithms, organizations can process vast and diverse datasets in real-time, generating actionable insights that enhance operational efficiency and competitive advantage. The study highlights key benefits, including improved financial forecasting accuracy, enhanced fraud detection capabilities, and more agile resource allocation. It also addresses the challenges associated with data integration, quality, and privacy, emphasizing the need for robust governance and ethical frameworks. Furthermore, the evolving role of accountants in a data-driven landscape is explored, underscoring the importance of data literacy and interdisciplinary collaboration. Ultimately, the integration of big data analytics into accounting processes not only optimizes financial operations but also positions the profession as a strategic driver of organizational success.